2007
DOI: 10.2478/s11536-007-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts and applications of computer navigation in orthopedic trauma surgery

Abstract: AbstractNavigation has become widely integrated into regular endoprosthetic procedures, but clinical use of navigation systems in orthopaedic trauma has only been implemented in a few indications. Navigation systems enable an accuracy of 1 mm or 1 degree. Navigation can achieve higher precision when it is combined with different imaging modalities, including preoperative computer tomography (CT), intraoperative CT, two-dimensional fluoroscopy, and, recently, intraoperative thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…With the development of the 3-D C-arm, 3D FluoroNav gradually gained popularity in spinal surgeries. Though its image quality is lower than that of CT, 3D FluoroNav provides real-time three-dimensional images, which serves as both C-arm and CT-based navigation, and does not need registration [57,58].…”
Section: Navigation Methods For Pedicle Screw Insertionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of the 3-D C-arm, 3D FluoroNav gradually gained popularity in spinal surgeries. Though its image quality is lower than that of CT, 3D FluoroNav provides real-time three-dimensional images, which serves as both C-arm and CT-based navigation, and does not need registration [57,58].…”
Section: Navigation Methods For Pedicle Screw Insertionmentioning
confidence: 99%
“…On comparing the navigated and conventional methods, most studies indicated that CTNav increased the time for spinal surgeries [15,23,26,37,41,44]. This might be attributed to extra protocols such as preoperative images, modeling and simulation, and registration [12,40,57,58]. One of the drawbacks of the CTNav is the considerable learning curve in the registration process.…”
Section: Other Perioperative Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although recent developments in computer assisted technologies have improved objective accuracy by use of a navigation system, its indications are still limited [11], [12]. We have attempted to apply navigation assistance for debridement arthroplasty to gain an accurate bony morphometric evaluation during the operation and to quantitatively resect osteophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Echnologically-advanced surgical platforms exploit navigation and/or robotic systems to improve the outcome of procedures in several fields, such as orthopedic surgery [1], abdominal surgery [2], and neurosurgery [3]. A. Enquobahrie is with Kitware Inc., Carrboro, NC, USA Thus, the need for different sensors in the operating room (OR) has highly increased in the past two decades with the purpose of improving the accuracy and the safety of surgical procedures for both patients and operators.…”
Section: Introductionmentioning
confidence: 99%